Training for organizational transformation - Lynton, Rolf P; Pareek, Udai (New Delhi Sage, 2000)
Rolf P Lynton`s book `Training for Organizational transformation` emphasises on remapping training routine.In fact,its main concern has shifted away from improving the training of individuals to contributing to the good functioning and continuation of org
Contents: Pt.1. for training, consultants and principals
Keywords: Employees-Training of; Organizational change